Gloss to the judgment of the Appeal Court in Gdańsk of 14 March 2022, III AUa 319/22 - Lewandowski, Piotr (Studia Iuridica Toruniensia, 2023)
The subject of the judgement with commentaries is the issue of a “dezubekizacyjna case” pending in court in connection of effectiveness of pension benefits’ lowering to officers of special forces. The Appeal Court has quashed a favorable sentence for an officer. Its sentence has been based on notorious facts that allow statements with no proof. The author’s opinion is that this happened in violation of procedural regulations and substantive law.